THE ADVANTAGES OF THE IMPLEMENTATION OF DIGITAL FLOW IN THE WORKING TIME MANAGEMENT OF DENTAL PROSTHESES RESTORATIONS - Andreea Codruta Novac; Daniela Maria Pop; Alina Tănase; Cristian Zaharia; Emanuela Lidia Crăciunescu; Mihai Romînu; Meda Lavinia Negruțiu; Virgil-Florin Duma; Cosmin Sinescu (Romanian Society of Oral Rehabilitation, 2023)
The aim of the study is to perform a comparison between conventional impression versus intraoral and extraoral scanning, plaster models compared to virtual and printed models, in terms of working time and fidelity. Material and method: The study evaluates two groups of practitioners: 30 dentists and 30 dental technicians, regarding registration and reproduction of the prosthetic field. The time required to perform the operations was evaluated in relation to variables that can influence the final results. Conventional impressions were monophasic and biphasic. In the digital flow, an intraoral scanner (Medit, i700) and a laboratory scanner (Medit T310) were used. Also, a printing machine (Elegoo Saturn) was used to print the models. Results and discussions: The average time allocated for conventional impressions is between 8min and 20sec and 25min and 40sec. The scanning time varied between 5 min 30 sec and 12 min 40 sec. Conclusions: The digital impression requires less working time compared to the conventional one, the latter cannot be completely abandoned, at least in terms of mobile prostheses. The fidelity of the prosthodontic field reproduction influences the adaptation of the restorations.